Apolipoprotein E genotypes are associated with diabetic peripheral neuropathy in Lebanese adults with type 2 diabetes: a case-control study - Nemr, Rita; Zidi, Sabrina; Echtay, Akram; Racoubian, Eddie; Beydoun, Nisrine; Almawi, Wassim Y. (Frontiers in Endocrinology, 2025)
BackgroundApolipoprotein E (ApoE) affects lipid metabolism and was associated with type 2 diabetes mellitus (T2DM) complications, including diabetic peripheral neuropathy (DPN). Despite improved glycemic control, DPN prevalence continues to rise, indicating mechanisms beyond hyperglycemia. We assessed the association between APOE genotypes and DPN susceptibility in patients with T2DM, focusing on dyslipidemia-linked pathways underlying neuropathy susceptibility distinct from glycemic effects.MethodsThe case-control study included 908 Lebanese patients with T2DM (382 with DPN, 526 without) and 695 healthy controls who underwent multimodal DPN assessment (NCS, QST, and MNSI). APOE genotyping was performed by PCR-RFLP analysis. Logistic regression models were applied to examine the associations between APOE variants and higher odds of DPN.ResultsT2DM patients showed significantly higher frequencies of ϵ2 and ϵ4 alleles than controls. Among T2DM patients, those with DPN had significantly higher ϵ2 allele frequency and lower ϵ3 allele frequency. At the genotype level, ϵ3/ϵ3 genotype demonstrated lower odds of DPN, while ϵ2/ϵ3, ϵ2/ϵ4, and ϵ3/ϵ4 were significantly associated with increased odds after adjustment for traditional risk factors. When pooled by allele, ϵ2-containing genotypes (ϵ2/ϵ3 + ϵ2/ϵ4; OR (95% CI) = 1.86 [1.38–2.51], and ϵ4-containing genotypes (ϵ3/ϵ4 + ϵ4/ϵ4 + ϵ2/ϵ4; OR (95% CI) = 1.62 [95% CI = 1.08–2.44]) showed high odds of DPN. Lipid profiles varied by genotype: ϵ4-containing genotypes displayed atherogenic patterns (elevated total cholesterol and triglycerides, reduced HDL) and were associated with a 1.6-fold higher odds of DPN, while ϵ2-containing genotypes showed increased total cholesterol and LDL among DPN patients. Genotype-specific clinical correlations were genotype-specific: ϵ3/ϵ3 was associated with retinopathy and hypertension but protective against nephropathy, while ϵ3/ϵ4 correlated with diabetic complications and dyslipidemia, and ϵ4/ϵ4 linked to a higher BMI.ConclusionAPOE genetic variants, especially ϵ4-containing genotypes, are associated with DPN susceptibility among Lebanese T2DM patients, independent of traditional risk factors including glycemic control. These population-specific findings require validation in prospective cohorts before clinical use but indicate potential value for APOE genotyping in DPN precision-risk models.